Predictors of Staphylococcus aureus Colonization and Results after Decolonization - Malcolm, Tennison L.; Robinson, Le Don; Klika, Alison K.; Ramanathan, Deepak; Higuera, Carlos A.; Murray, Trevor G. (Interdisciplinary Perspectives on Infectious Diseases, 2016)
Protocols for the screening and decolonization of Staphylococcus aureus prior to total joint arthroplasty (TJA) have become widely adopted. The goals of this study were to determine: (1) whether implementation of a screening protocol followed by decolonization with mupirocin/vancomycin and chlorhexidine reduces the risk of revision compared with no screening protocol (i.e., chlorhexidine alone) and (2) whether clinical criteria could reliably predict colonization with MSSA and/or MRSA. Electronic medical records of primary patients undergoing TJA that were screened (n=3,927) and were not screened (n=1,751) for Staphylococcus aureus at least 4 days prior to surgery, respectively, were retrospectively reviewed. All patients received chlorhexidine body wipes preoperatively. Patients carrying MSSA and MRSA were treated preoperatively with mupirocin and vancomycin, respectively, along with the standard preoperative antibiotics and chlorhexidine body wipes. Screened patients were 50% less likely to require revision due to prosthetic joint infection compared to those not screened (p=0.04). Multivariate regression models were poorly accurate in predicting colonization with MSSA (AUC = 0.58) and MRSA (AUC = 0.62). These results support the routine screening and decolonization of S. aureus prior to TJA.